GOAT RUMINAL ARTERY IS MORE SELECTIVE TO EXOGENOUS NITRIC OXIDE DONORS THAN ENDOGENOUS NITRIC OXIDE - DASH, JEEVAN RANJAN; PARIJA, SUBASH CHANDRA (The Bioscan, 2013)
This study was conducted to study the property of goat ruminal artery towards the exogenous nitric oxidedonor SIN-1 and endogenous nitric oxide generator acetylcholine in NA, 10µM induced contraction. The isolated ruminal arterial rings of goat with intact endothelium were perfused in organ bath and isometric contraction was studied. (1) Noradrenalin (NA), 10µM produced a potent vasotonic response with threshold concentration and Emax3×10-7M and 3×10-5M, respectively (2) 3-morpholinosydnonimine (SIN-1) produced significant relaxation (Emax= 38.31±7.48, EC50=2.54 µM, n=6) than acetylcholine (ACh) (Emax= 70.21±5.49, EC50 max= 30.24 µM, n=9). (3) L-Arginine preincubation found to have no significant effect (Emax= 32.34±2.72, n=6) on SIN-I induced relaxation. Similarly L-NAME had no effect. But ODQ potently blocked SIN-I relaxation (Emax= 91.04±8.39, n=6). From the above observations it is concluded that NO donor SIN-I is a more potent relaxing agent than acetylcholine in goat ruminal artery.The observed effect of SIN-1 in this artery is due to activity of soluble guanylatecyclase and has no prominent NOS (Nitric oxide synthase) activity.